2021
DOI: 10.1111/his.14597
|View full text |Cite
|
Sign up to set email alerts
|

The Bowel Cancer Screening Programme Expert Board: an analysis of activity during 2017–2020

Abstract: Aims:The inception of the National Health Service Bowel Cancer Screening Programme in England in 2006 highlighted the fact that the differential diagnosis between the presence of epithelial misplacement and adenocarcinoma occurring in colorectal adenomas is problematic. The pathology Expert Board (EB) was created to facilitate the review of difficult cases by a panel of three experienced gastrointestinal pathologists. This article describes a review of the work of the EB over a 4-year period (2017-2020). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…7 Interobserver agreement was found to be better between panel members than between the panels and the referrers. 6,7 This is similar to previous studies and presumably reflects the greater levels of experience in the assessment of these polyps by panel members, who will be specialist gastrointestinal pathologists. 10 The English panel was set up with three members in order to maximize the chance of creating an opinion that is at least a consensus based on a 2:1 majority.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…7 Interobserver agreement was found to be better between panel members than between the panels and the referrers. 6,7 This is similar to previous studies and presumably reflects the greater levels of experience in the assessment of these polyps by panel members, who will be specialist gastrointestinal pathologists. 10 The English panel was set up with three members in order to maximize the chance of creating an opinion that is at least a consensus based on a 2:1 majority.…”
supporting
confidence: 82%
“…Bateman et al found that their panel changed a malignant to a benign diagnosis in 50% of polyps referred with the former diagnosis (to the nearest whole percent). 6 Smits et al found a 'discrepancy' rate between their panel and referring pathologists of 39% in adenomas and 53% of adenocarcinomas (to the nearest whole percent). Within the 'adenoma' group, most of the discrepancies were in the adenoma type and the grade of dysplasia.…”
mentioning
confidence: 98%
See 3 more Smart Citations